Information System for Calculating Medical Record Personnel in the Industrial Revolution Era 4.0 - Al hadri, Cecilia Farrona; Sunandar, Ahmad (Jurnal AKSI (Akuntansi dan Sistem Informasi), 2021)
Medical recorders and health information are some of the health workers who are included in the "medical technical" group where the task of medical recorders and health information is to manage patient data into health information that is useful for decision making. Planning for the needs of health personnel must be following the needs in the field in terms of type, qualification, quantity, and procurement. Excess health personnel will result in unproductive use of work time, while a shortage of health workers will result in excessive workloads so that in planning the needs of health workers an analysis of the workload is required. This study was conducted to obtain information on the ideal number of medical record health personnel using workload calculations. This research method is based on the calculation method of Work Load Indicator Staff Need (WISN) through the implementation of a website-based information system at XYZ Hospital. Based on the results of this study, it shows that the ratio of <1 HR in the unit is not sufficient and not following the workload, namely the number of human resources in the Old Patient TPPRJ with a ratio value of 0.33; RJ coding ratio value 0.41; and Analysis with a ratio value of 0.38. Lack of officers at TPPRJ for Old Patients, RJ Coding, and Analysis resulted in poor service, so it is necessary to add medical personnel to that section when conditions are crowded.